Microwave Assisted Demulsification of Iraqi Crude Oil Emulsions Using Tri-octyl Methyl Ammonium Chloride (TOMAC) Ionic Liquid - A.M. Mohammed, Sawsan; K. Salih, Watheq (Iraqi Journal of Chemical and Petroleum Engineering, 2014)
In the present work, the efficiency of Tri-octyl Methyl Ammonium Chloride (TOMAC) ionic liquid was investigated as new and green demulsifier for three types of Iraqi crude oil emulsions (Nafut Khana (NK), Kirkuk and Basrah). The separation efficiency was studied at room temperature and by using microwave heating technique. Several batch experiments were done to specify the suitable conditions for the emulsification and demulsification which were specified as 45 minutes and 3000 rpm for crude oil emulsification while the ionic liquid doses were (500,300,150,50) ppm and the conditions of microwave heating were 1000 watt and 50 second as irradiation time. The results were very encouraging especially for NK and Kirkuk crude oil emulsions where the separation efficiency was between (100%-95%) in both cases (by microwave heating and at room temperature demulsification). The separation percentages of Basrah crude emulsion varied but as a general result, the efficiency was acceptable for high doses at the same time, while for low doses, the water removal ratio was not good as the previous one.